An Investigation of The Velar Nasal in Badini Kurdish Dialect - Saeed, Saeed A.; Naser, Laureen I. (Humanities Journal of University of Zakho, 2017)
The velar nasal, also called "Engma" or "Angma", can be found in the phonologicalinventories of many languages across the world. Kurdish researchers vary in their opinions as to whether this sound is listed among the inventory of Kurdish language phonemes or not. Some researchers have tackled this case in Sorani Kurdish but research in Badini is scarce in this area. In this paper we aim to investigate the velar nasal /N/ in Badini Kurdish, which is a very controversial topic. The paperaims to answer the question as to whether it can be considered as a phoneme or it is just an allophonic realization of the alveolar nasal /n/ when followed by the voiced velar stop/g/. This is done through providing examples that have the combination of (n+g) which have a possible occurrence of the velar nasal. These examples are first analyzed articulatory in terms of some phonological processes such as assimilation, morpheme affixation, and syllabification. They are then analyzed acoustically by contrasting the pairs and searching for nasal bands using Praat. After analyzing both articulatory and acoustic data, it was concluded that the velar nasal can be found in Badini Kurdish but only as an allophone of the alveolar nasal which is the result of certain phonological rules such as assimilation and co-articulation. They are in free variation and couldn’t change the meaning. So, we can’t consider it as a distinct phoneme in this dialect.